2017
DOI: 10.1007/s10645-017-9290-y
|View full text |Cite
|
Sign up to set email alerts
|

Early Smoking, Education, and Labor Market Performance

Abstract: This study investigates the effects of early smoking on educational attainment and labor market performance by using mixed ordered and mixed proportional hazard models. The results show that early smoking adversely affects educational attainment and initial labor market performance, but only for males. The probability to finish a scientific degree is 4%-point lower for an early smoker. The effect of early smoking on initial labor market performance is indirect through educational attainment. Once the indirect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…where r ∈ (0, 1) is a random number here and r 0 ∈ (0, 1) is the constant value set at the beginning of the loop. When it is r > r 0 , the calculation of the probability of ants transferring from city x to city y is still consistent with formula (1) [18]. In addition to the two above improvements, the ant colony system also needs to update the pheromone in the part where the ant colony finds the path.…”
Section: Improved Algorithm Of Ant Colony Algorithmmentioning
confidence: 73%
“…where r ∈ (0, 1) is a random number here and r 0 ∈ (0, 1) is the constant value set at the beginning of the loop. When it is r > r 0 , the calculation of the probability of ants transferring from city x to city y is still consistent with formula (1) [18]. In addition to the two above improvements, the ant colony system also needs to update the pheromone in the part where the ant colony finds the path.…”
Section: Improved Algorithm Of Ant Colony Algorithmmentioning
confidence: 73%
“…Using nationally representative data from the Netherlands, a 2015 study found that early smoking onset among men, but not among women, adversely affects educational performance, which later results in lower labor market performance. In addition, early onset of cigarette use reduced labor market performance even after controlling for education and other socio-economic characteristics (Palali 2015).…”
Section: Empirical Evidencementioning
confidence: 98%